Evaluation of the Effect of Silver Diamine Fluoride Treatment with and without Glutathione and Potassium Iodide on the Micro-shear Bond Strength of CR to Primary Tooth Dentin - Khataminia, Masoumeh; Emami, Akramsadat; Basir, Leila (Galen Medical Journal, 2025)
Background: Silver diamine fluoride (SDF) is widely employed to halt caries in juvenile or uncooperative children due to its antimicrobial and remineralizing properties. Despite its effectiveness, SDF causes dark discoloration of treated dentin, raising esthetic concerns. Potassium iodide (KI) and glutathione (GSH) have been proposed as adjuncts to reduce discoloration; however, their influence on subsequent adhesive bonding to primary dentin remains unclear. This study evaluated and compared the micro-shear bond strength (μSBS) of composite resin (CR) to demineralized primary tooth dentin treated with SDF alone, SDF combined with KI or GSH, and untreated dentin. Materials and Methods: Fifty-two sound primary teeth were prepared to obtain flat mid-coronal dentin surfaces and artificially demineralized. Specimens were randomly assigned to four groups (n=13): control (no SDF), SDF, SDF+KI, and SDF+20% GSH. After pretreatment, all samples underwent phosphoric acid etching, application of a total-etch adhesive, and restoration with CR using standardized molds. μSBS was measured with a universal testing machine operating at a crosshead displacement rate of 1 mm/min. Statistical evaluation of the data was conducted via one-way analysis of variance (ANOVA) followed by Tukey’s post-hoc comparisons, with the significance level set at 0.05. Results: SDF-treated groups demonstrated significantly higher μSBS values compared with the control group (P<0.001). Mean bond strengths were highest for SDF alone, followed closely by SDF+KI and SDF+GSH. The data revealed no meaningful divergence in the outcomes of the three SDF-based treatments. Conclusion: Pretreatment of demineralized primary dentin with SDF significantly enhanced CR bond strength. The addition of potassium iodide or glutathione did not adversely affect bonding performance, suggesting these agents may be used to reduce discoloration without compromising adhesive outcomes.